2020
DOI: 10.7150/jca.40621
|View full text |Cite
|
Sign up to set email alerts
|

The Prediction of Survival in Hepatocellular Carcinoma Based on A Four Long Non-coding RNAs Expression Signature

Abstract: Prognostic stratification in hepatocellular carcinoma (HCC) patients is still challenging. Long non-coding RNAs (lncRNAs) have been proven to play a crucial role in tumorigenesis and progression of cancers. The aim of this study is to develop a useful prognostic index based on lncRNA signature to identify patients at high risk of disease progression. We obtained lncRNA expression profiles from three publicly available datasets from Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA). By the risk s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…(B) Disease-free survival (DFS) for the high- and low-risk patients. (C) The ROC analysis of OS outcomes for the five-AR-lncRNA signature (TMCC1-AS1, PLBD1-AS1, MKLN1-AS, LINC01063, CYTOR) by us; five-autophagy-related gene (ARG) signature (HDAC1, RHEB, ATIC, SPNS1, and SQSTM1) by Huo et al ( 2020 ); four-lncRNA signature (ENSG00000234608, ENSG00000242086, ENSG00000273032, ENSG00000228463) by Yang et al ( 2020 ) and four-lncRNA signature (RP11-322E11.5, RP11-150O12.3, AC093609.1, CTC-297N7.9) by Wang et al ( 2017 ) (D) Kaplan–Meier curves of patients stratified by different clinicopathological traits. Hepatitis B virus, HBV; hepatitis C virus, HCV.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(B) Disease-free survival (DFS) for the high- and low-risk patients. (C) The ROC analysis of OS outcomes for the five-AR-lncRNA signature (TMCC1-AS1, PLBD1-AS1, MKLN1-AS, LINC01063, CYTOR) by us; five-autophagy-related gene (ARG) signature (HDAC1, RHEB, ATIC, SPNS1, and SQSTM1) by Huo et al ( 2020 ); four-lncRNA signature (ENSG00000234608, ENSG00000242086, ENSG00000273032, ENSG00000228463) by Yang et al ( 2020 ) and four-lncRNA signature (RP11-322E11.5, RP11-150O12.3, AC093609.1, CTC-297N7.9) by Wang et al ( 2017 ) (D) Kaplan–Meier curves of patients stratified by different clinicopathological traits. Hepatitis B virus, HBV; hepatitis C virus, HCV.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 1 , in the present study, after applying weighted correlation network analysis (WGCNA) and several kinds of Cox regression analysis on the database of HCC patients in The Cancer Genome Atlas (TCGA), five AR lncRNAs (TMCC1-AS1, PLBD1-AS1, MKLN1-AS, LINC01063, and CYTOR) were identified to construct a prognostic signature for the overall survival (OS) outcomes of HCC patients. The sensitivity and specificity of the five-AR-lncRNA signature surpassed three recently published prognostic signatures for HCC (Wang et al, 2017 ; Huo et al, 2020 ; Yang et al, 2020 ). Furthermore, significant differences were found in the therapeutic outcomes, including immunotherapy and chemotherapy responses, between the high- and low-risk groups.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…It appears that such individual biomarkers are limited because they can be in uenced by many factors, rendering their predictive ability unstable; thus, other recent studies have shown that combined analysis of a panel of biomarkers is the most promising approach to change clinical management (40,41). With respect to HCC, since the accuracy of various prognostic models still varies, the eld currently warrants further research (19)(20)(21). In the present study, the LASSO Cox regression model was used to select the most useful prognostic markers from many genes related to HCC.…”
Section: Discussionmentioning
confidence: 99%
“…developed a four-long non-coding RNA signature as a novel candidate biomarker for prognosis in HCC patients (AUC: 0.689; 95% CI: 0.617-0.761; P < 0.01) (21). Nevertheless, due to the varying quality of prediction models, the construction of an optimal prognostic model remains a hot topic.…”
Section: Introductionmentioning
confidence: 99%